Denisiuk-type reflection holography display with sillenite crystals for imaging and interferometry of small objects - Barbosa, E. A. [UNESP]; Preto, A. O. [UNESP]; Silva, D. M. [UNESP]; Carvalho, J. F.; Morimoto, N. I. (Elsevier B.V., 2008)
A novel setup for imaging and interferometry through reflection holography with Bi12TiPO20(BTO) sillenite photorefractive crystals is proposed. A variation of the lensless Denisiuk arrangement was developed resulting in a compact, robust and simple interferometer. A red He-Ne laser was used as light source and the holographic recording occurred by diffusion with the grating vector parallel to the crystal [0 0 1]-axis. In order to enhance the holographic image quality and reduce noise a polarizing beam splitter (PBS) was positioned at the BTO input and the crystal was tilted around the [0 0 1]-axis. This enabled the orthogonally polarized transmission and diffracted beams to be separated by the PBS, providing the holographic image only. The possibility of performing deformation and strain analysis as well as vibration measurement of small objects was demonstrated. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: holography; reflection holograms; photorefractive materials